BUSINESS MANAGEMENT IN TIMES OF THE PANDEMIC: THE IMPACT OF COVID-19 ON THE PERFORMANCE OF DIGITIZED SMES (S) - EL FAKID, Asmaa; ALOUANE, Sara; ECHAOUI, Abdellah (Revue Internationale du Chercheur, 2021)
It is becoming increasingly difficult to ignore the importance of the small and medium-sized enterprise sector in the economic and social development of a country. The contribution of a vibrant SME sector to the economies of countries has long been accepted around the world, and is seen as an incubator for jobs, innovation and growth (OECD, 2020). The objective of this research is to understand the effects of the crisis produced by the Corona Virus on the business activity of SMEs. Our survey was administered in collaboration with executives from two digitized companies, from different sectors of activity, during the months of March, April, May, June, and July 2020. Through several theoretical and literature events, this article aims to answer the following main question: To what extent does the Covid 19 pandemic impact the performance of digitized companies? Through, a general reading of post-pandemic economies, as well as the consequences of this latest crisis on the performance of digitized SMEs (S).